Theories of Learning and Their Relation to the Development of the Islamic Religious Education Curriculum - Anton Rohmat Basuki; Hanifan Islami (KIPS Institute, 2025)
This research aims to analyze learning theories and their relevance in the development of the Islamic Education Curriculum (PAI). Through a literature study approach, this research examines various learning theories such as behaviorism, cognitivism, constructivism, and humanism, as well as their implications for the design of the PAI curriculum. The results of the research show that the integration of learning theories in the development of the PAI curriculum can enhance learning effectiveness, meet student needs, and accommodate Islamic values. This study also highlights the importance of a multidisciplinary approach in designing an adaptive PAI curriculum that addresses the challenges of the times.